2017
DOI: 10.1001/jamaophthalmol.2017.4868
|View full text |Cite
|
Sign up to set email alerts
|

Vision Loss Associated With the Opioid Epidemic

Abstract: most commonly selected preferred treatment, many respondents indicated that more evidence was needed to guide treatment choices. 4 The MUTT I result was driven primarily by ulcers caused by Fusarium, which had the worst response to voriconazole. 1 After the results of MUTT I and 2 subsequent trials, 2,3 only a few experts indicated that they would prefer to treat Fusarium keratitis with voriconazole. Limitations of this study include that respondents self-reported practice patterns and it was not possible to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…While opioids have proven effective analgesics in a wide range of ophthalmic settings, attention is turning to how they are used in ophthalmology . Patel and Sternberg conducted a study characterizing opioid-prescription patterns by ophthalmologists within Medicare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While opioids have proven effective analgesics in a wide range of ophthalmic settings, attention is turning to how they are used in ophthalmology . Patel and Sternberg conducted a study characterizing opioid-prescription patterns by ophthalmologists within Medicare.…”
Section: Introductionmentioning
confidence: 99%
“…4 While opioids have proven effective analgesics in a wide range of ophthalmic settings, attention is turning to how they are used in ophthalmology. [5][6][7][8][9][10] Patel and Sternberg 11 conducted a study characterizing opioid-prescription patterns by ophthalmologists within Medicare. They showed that about 90% of ophthalmologists wrote fewer than 10 opioid prescriptions annually, and approximately 1% wrote more than 100 prescriptions annually.…”
mentioning
confidence: 99%
“…3 Up to 80% of heroin users first misused prescription opioids, and an estimated 4 to 6% of patients who misuse opioids eventually transition to heroin. 4,5 In addition to potential overdose death, this behavior increases the risk of life-threatening complications such as sepsis, hepatitis C, HIV, and vision-threatening complications from endophthalmitis. [4][5][6][7][8] Bearing in mind current opioid prescribing trends, it is important to consider the relationship between opioid prescribing patterns and medical specialty.…”
mentioning
confidence: 99%
“…4,5 In addition to potential overdose death, this behavior increases the risk of life-threatening complications such as sepsis, hepatitis C, HIV, and vision-threatening complications from endophthalmitis. [4][5][6][7][8] Bearing in mind current opioid prescribing trends, it is important to consider the relationship between opioid prescribing patterns and medical specialty. To date, there has been no investigation into the pattern of opioid prescribing by optometrists.…”
mentioning
confidence: 99%
See 1 more Smart Citation